2003
DOI: 10.1021/ja028462v
|View full text |Cite
|
Sign up to set email alerts
|

E Stereoregular 1,1 and 1,3 Constitutional Units from 1,3-Butadiene in Copolymerizations Catalyzed by a Highly Hindered C2 Symmetric Metallocene

Abstract: Unprecedented 1,1 and 1,3 constitutional units from 1,3-butadiene, both presenting only the E configuration of the double bond, have been achieved by copolymerization with ethene, conducted at high temperature and low ethene concentration, when catalyzed by a highly hindered C(2) symmetric metallocene. Ethene/butadiene copolymerizations by this catalyst generally lead to prevailing methylene-1,2-cyclopropane units from butadiene. Polymer microstructures obtained for different comonomer concentrations clearly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 35 publications
4
56
0
Order By: Relevance
“…E. Probably, catalysts (2) and (3) , the ethene insertion becomes very fast and it usually competes with the D ! G rearrangement, leading to F. [2,3] But, as for catalysts (2) and (3), the D ! F reaction is anyway slowed down by the high steric hindrance of the substituents and the main products, both at high and at low [E], come from the D !…”
Section: Ethene-13-butadiene Copolymerizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…E. Probably, catalysts (2) and (3) , the ethene insertion becomes very fast and it usually competes with the D ! G rearrangement, leading to F. [2,3] But, as for catalysts (2) and (3), the D ! F reaction is anyway slowed down by the high steric hindrance of the substituents and the main products, both at high and at low [E], come from the D !…”
Section: Ethene-13-butadiene Copolymerizationsmentioning
confidence: 99%
“…Recently, we have shown that copolymerization of 1,3-butadiene with ethene, catalyzed by the isospecific catalytic system based on the C 2 symmetric zirconocene rac-[CH 2 -(3-tert-butyl-1-indenyl) 2 ]ZrCl 2 , activated by MAO, leads to polyethenes containing methylene-1,2-cyclopropane Copolymerization performed utilizing 13 C-labeled butadiene [5] and molecular modeling calculations [2][3][4] contributed to rationalize the observed behavior for copolymerizations catalyzed by these C 2 symmetric metallocene complexes. For all the considered metallocene complexes having substituents in positions 3 and 3 0 , minimum energy coordination intermediates and insertion transition states have been located for the primary Z 2 coordination of butadiene, which leads through a primary vinyl insertion to a s-coordinated growing chain (step A !…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…η2 primary coordination of butadiene leads to formation of vinyl groups or rings through a primary vinyl insertion, whereas η2 secondary and η4-cis coordination of butadiene leads to trans and cis 1,4-butadiene units through the formation of a syn-η3-coordinated growing chain and an anti-η3-coordinated growing chain, respectively [6][7][8][9]. Until now, reports on olefin/butadiene copolymerization, where the insertion reaction of the 1,3-butadiene proceeds via 1,2-insertion preferentially to form a vinyl group, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] As it has been reported in the literature, PEs containing controlled amounts of methylene-1,2-cyclopropane and methylene-1,2-cyclopentane units (hereafter called E-C3) can be obtained by the polymerization of ethene with 1,3-butadiene using rac-[CH 2 (3-tert-butyl-1-indenyl) 2 ]ZrCl 2 activated by methylalluminoxane as a catalyst. [8][9][10][11][12] These PEs are technologically relevant because the presence of reactive cyclopropane rings in the chains discloses the possibility to obtain polymers with different properties. 13,14 For example, in a recent study by our group, we showed that it is possible to produce crosslinked PE by simple thermal treatments of E-C3 copolymers in the temperature range of 160-200 1C.…”
Section: Introductionmentioning
confidence: 99%